Paper and Pencil in the Age of BIM. Issue 4 (2nd October 2018) - Tanner, Peter; Bellod, Juan Luis; Sanz, David
Abstract: Many key aspects of bridge design are governed by site-related, geometric, functional and constructional constraints. Economy is yet another decisive factor in public works, whilst enhanced sensitivity to aesthetics is driving the demand for more than merely utilitarian structures. Such exacting boundary conditions often spur careful or even innovative structural design. Since the successful translation of numerous constraints into a reliable, functional, cost-effective structure with aesthetic appeal is primarily a question of sound conceptual design, the importance of this step in the design process as a whole cannot be overstated. This paper summarises the more prominent aspects of conceptual bridge design, particularly in connection with meeting and duly balancing non-standardised economy- and aesthetics-related objectives. Taking the outcome of the conceptual design stage as a starting point, the paper also addresses the use of digital design tools for the development of other construction documents. By way of illustration, the ideas underlying the conceptual design for the Butarque footbridge in Leganés, Spain are discussed, in connection primarily with the specific boundary conditions but also with the actual layout, detailing and construction. The example shows that a modern, technologically advanced design may be compatible with a solution whose elegance meets the most exacting aesthetic standards. It also shows that when the conceptual approach is well thought out, the solution is subject to only minor change in subsequent design stages.